MEDIA PEMBELAJARAN PENGENALAN ANGGOTA TUBUH MANUSIA PADA ANAK PENDERITA TUNA GRAHITA DI SLB PROF. DR. SRI SOEDEWI MASCJHUN SOFWAN, SH: Media, Media of learning, The introduction, Members of the human body, Adobe Flash CS6 - -, Elzas (JURNAL AKADEMIKA, 2019)
The child's mental retardation is one of the children in need special impaired her mental development was caused because of low level of intelligence of the child. This research aims to produce a multimedia-based learning media on lessons introduction members of the human body on the SLB Prof. Dr. Sri Soedewi Mascjhun Safwan, SH for child mental retardation, so as to provide benefits to children Mental retardation, and also adds another alternative in learning. The design of multimedia application is done through the stages survey spaciousness to the needs of the multimedia model is needed, also carried out an adjustment with the literature-literature provided by the school. The application of learning media introduction of the members of the human body. the material contained on the nose, eyes, ears, mouth, Hands and Feet are equipped also with evaluation and profile. Researchers are designing learning media introduction of the members of this body with the software Adobe Flash CS6. The results of this research is to Study the introduction of Media members of the human body on Child sufferers of mental retardation in SLB Prof. Dr. Sri Soedewi, Safwan Mascjhun SH.